Increased ex vivo antigen presentation profile of B cells in multiple sclerosis. (May 2017) - Mathias, Amandine; Perriard, Guillaume; Canales, Mathieu; Soneson, Charlotte; Delorenzi, Mauro; Schluep, Myriam; Du Pasquier, Renaud A
Background: Multiple sclerosis (MS) is thought to be T cell mediated but the mechanisms eliciting such a dysregulated adaptative immune response remain enigmatic. Objective: To examine the activation profile of antigen-presenting cells (APCs) in MS. Methods: A total of 98 study subjects were enrolled including patients suffering from relapsing–remitting, secondary- and primary-progressive (PP) MS, other inflammatory neurological diseases, and healthy controls. Blood monocytes and B cells were stimulated using specific ligands of toll-like receptors (TLRs) or inflammasomes or Epstein–Barr virus (EBV) particles. Their activation profile was determined before or after stimulation by flow cytometry (CD40, CD80, CD83, CD86, and human leukocyte antigen–antigen D related (HLA-DR)) and Luminex assay, measuring the concentration of eight cytokines in culture supernatants. Differences among groups were assessed in a linear model framework. Results: We demonstrate that relapsing MS patients exhibit an increased expression of HLA-DR and CD40 ex vivo, mostly at the surface of B cells. Specific stimulations of TLR or inflammasomes enhance the expression of components of the immunological synapse and the cytokine secretion but without differences between categories of study subjects. Conclusion: These data suggest that the activation profile of B cells is increased in MS. However, the perception of the danger signal by B lymphocytes and monocytes does not seem to be different in MS patients as compared to control subjects.